2021
DOI: 10.3390/ma14051253
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Life of 7005 Aluminum Alloy Cruciform Joint Considering Welding Residual Stress

Abstract: An evaluation method is proposed for determining the full fatigue life of aluminum alloy cruciform joint, including the crack initiation and propagation with welding residual stress. The results of simulations have shown that the boundary between the initiation and propagation stage is not constant, but a variable value. The residual stress leads to a significant reduction in both stages, which is more severe on initiation. With considering residual stress, the ratio of crack initiation to total life is below … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Several scholars have analyzed the crack propagation and residual life of different structures. [6][7][8][9][10][11][12][13] He 14 provided a method for predicting the crack path of welded joints. The influence of the yield strength on the crack propagation path of the welded joint was analyzed without considering other mechanical properties and residual stress.…”
Section: Introductionmentioning
confidence: 99%
“…Several scholars have analyzed the crack propagation and residual life of different structures. [6][7][8][9][10][11][12][13] He 14 provided a method for predicting the crack path of welded joints. The influence of the yield strength on the crack propagation path of the welded joint was analyzed without considering other mechanical properties and residual stress.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al build a numerical model by XFEM and experimental investigation of crack growth in T-joints to better understand the mechanisms of crack growth in welded joints [4]. Wang et al also used XFEM for numerical simulation of the fatigue crack growth and suggested developing simple solutions for practical prediction of k M factors [5]. XFEM will be utilized to make a model of a semi-elliptical weld toe crack in a fillet weld for different sizes.…”
Section: Introductionmentioning
confidence: 99%